Paradoxical Strategies and Firm Performance: The Case of Indonesian Banking Industry - Hamsal, Mohammad; Agung, I Gusti Ngurah (UI Scholars Hub, 2007)
Recently, research on paradoxical strategies has been considered critical in winning in the competitive dynamic landscape, characterized by uncertainty and rapid changes in the business environment. Such environmental uncertainties require firm to apply paradoxical strategies; combining strategic flexibility and strategic consistency (Parnell, 1994). This study addresses three main questions: what is the effect of strategic flexibility on firm’s performance; what is the effect of strategic consistency on firm’s performance; what is the contingent effect of perceived environmental uncertainty on the relationship between paradoxical strategies and firm’s performance. Questionnaires were distributed to 131 CEOs or members of top management team of Indonesian commercial banks (including sharia banks); and the 59 returned responses were analyzed to test hypotheses. The results indicate that strategic flexibility has positive effect on bank‘s performance, while strategic consistency does not have significant effect on bank’s performance. In terms of combining these two paradoxical strategies, the results of this study confirm that the effect of strategic flexibility on bank’s performance depends on strategic consistency and environmental uncertainty.